The Effect of Pesticide Residues on Environmental Quality in the Kromong II Watershed, Pacet District, Mojokerto Regency - Putra, Dimas Ganda Permana; Fitriyani, Zenita Afifah; Ardiyanto, Fahrur Rijal; Dewi, Yuni Rosita; Khusumawati, Titik; Alfarisy, Fariz Kustiawan; Novita, Mega Darmi; Soesanto, Soesanto (Journal of Applied Agricultural Science and Technology, 2025)
The river basin serves multiple ecological and socio-economic functions for the local community, particularly the Kromong II Watershed in Pacet District. A major issue in the upstream area of the watershed is the use of pesticides by local residents in agricultural land management. Excessive pesticide use leads to significant environmental residue accumulation. This study aimed to assess pesticide residue levels, evaluate the quality of irrigation water and soil fertility in rice fields, and map polluted locations using the ArcGIS 10.3 remote sensing application. The analysis was conducted at three designated research sites: Stations I, II, and III. Biochemical Oxygen Demand (BOD) was analyzed using the SNI 6989.72:2009 standard, while Chemical Oxygen Demand (COD) was measured following the SNI 6989.2029 method at the Mojokerto Regency Environmental Agency (DLH) Laboratory. Soil organic carbon (C-organic) was analyzed using the IKP-208 Organic Carbon Test, and total nitrogen (Total N) was determined through spectrophotometric analysis at the PT Graha Mutu Persada Laboratory. Metomil was analyzed using the Liquid Chromatography–Mass Spectrometry (LC-MS) method, while Profenofos was analyzed using Gas Chromatography–Mass Spectrometry (GC-MS). The study found that the highest levels of BOD and COD were recorded at Station III, with values of 11.4 mg/L and 28.6 mg/L, respectively. The highest total nitrogen (Total N) concentration was observed at Station I, measuring 0.14%, while the highest soil organic carbon (C-organic) content was found at Station III, at 7.87%. The LC-MS analysis of methomyl residues showed the highest concentration at Station III, with a value of 0.002 mg/L in irrigation water samples. Similarly, the GC-MS analysis of Profenofos residues indicated the highest concentration at Station II, measuring 8.25 ml/L. Based on these findings, it can be concluded that pesticide residue pollution, particularly from Profenofos, is most severe in the irrigation channel at Station II.